2017
DOI: 10.1002/ecm.1246
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle matters: DNA barcoding reveals contrasting community structure between fern sporophytes and gametophytes

Abstract: Ferns are the only major lineage of vascular plants that have nutritionally independent sporophyte (diploid) and gametophyte (haploid) life stages. However, the implications of this unique life cycle for fern community ecology have rarely been considered. To compare patterns of community structure between fern sporophytes and gametophytes, we conducted a survey of the ferns of the islands of Moorea and Tahiti (French Polynesia). We first constructed a DNA barcode library (plastid rbcL and trnH‐psbA) for the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 94 publications
(191 reference statements)
0
81
0
Order By: Relevance
“…Nitta et al. (), in the only study of fern community structure to date that has examined both gametophytes and sporophytes, found substantial differences between the two life stages in terms of species composition across sites. This study, like many other studies of fern diversity and community composition (Kluge and Kessler, , ; Watkins Jr. et al., ; Kluge et al., ; Salazar et al., ; Kessler et al., ), focused on changes in species composition and richness over an elevational gradient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nitta et al. (), in the only study of fern community structure to date that has examined both gametophytes and sporophytes, found substantial differences between the two life stages in terms of species composition across sites. This study, like many other studies of fern diversity and community composition (Kluge and Kessler, , ; Watkins Jr. et al., ; Kluge et al., ; Salazar et al., ; Kessler et al., ), focused on changes in species composition and richness over an elevational gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Nitta et al. () found that the level of phylogenetic clustering differed between the life stages and with elevation, with sporophytes showing evidence of phylogenetic clustering that grew stronger with increasing elevation, while gametophytes showed no evidence of phylogenetic clustering at any elevation. These authors also found, strikingly, that gametophytes showed no evidence of the mid‐elevation peak in species richness that is a hallmark of fern species distributions across elevational gradients in the tropics, based entirely on studies of sporophytes (Cardelus et al., ; Kluge and Kessler, ; Watkins et al., ; Kluge et al., ; Kessler et al., ; Pouteau et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Angiosperms are "functionally" diplontic because though there is a gametophytic stage, it is few-celled, does not undergo substantial haploid somatic development, and is dependent on the sporophyte. While different ploidies have been compared in angiosperm invasions (Bowen et al, 2017), diploid and polyploid angiosperms are not free-living stages of the same sexual life cycle, but are rather wholly separate life cycles (Wood et al, 2009) In contrast, ferns have dominant sporophytes, and the gametophyte stage (the prothallus) is small and is thought to be rarely seen in nature, but a recent study demonstrated that they are ecologically relevant in which sporophytic and gametophytic communities can differ in species composition and phylogenetic structure (Nitta, Meyer, Taputuarai, & Davis, 2017). Neither the fern gametophyte nor sporophyte is dependent on one another as in mosses or seed plants.…”
Section: Life C Ycle D Iver S It Ymentioning
confidence: 99%